1991
DOI: 10.1128/aac.35.12.2481
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fluconazole and amphotericin B for prevention and treatment of experimental Candida endocarditis

Abstract: Fluconazole and amphotericin B were compared in the prophylaxis and treatment of Candida albicans aortic endocarditis in a rabbit model. In the prophylaxis study, catheterized rabbits received, prior to intravenous (i.v.) challenge with C. albicans (2 x 107 blastospores), either no therapy, single-dose i.v. amphotericin B (1 mg/kg of body weight), single-dose fluconazole (50 mg/kg or 100 mg/kg i.v. or intraperitoneally [i.p.j), or fluconazole (50 mg/kg or 100 mg/kg i.v. or i.p.) with a second dose 24 h after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 14 publications
4
36
1
Order By: Relevance
“…However, although the serum levels were not tested, this possibility was contradicted by the fact that AmB was very effective at decreasing fungal densities in the kidneys. Moreover, previous studies using the same dosage of AmB in the endocarditis models also reported a very slow response of the infection (5,31,35,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…However, although the serum levels were not tested, this possibility was contradicted by the fact that AmB was very effective at decreasing fungal densities in the kidneys. Moreover, previous studies using the same dosage of AmB in the endocarditis models also reported a very slow response of the infection (5,31,35,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of polymorphonuclear phagocytes in endocarditis provides very stringent experimental conditions, and therapeutic success relies exclusively on the killing effect of the antimicrobial treatment. Given that previous studies of Candida experimental endocarditis described cure only after weeks of antifungal treatment, the sterilization of aortic valve vegetations recently reported in rats infected with parent strain CAF2-1 after a 5-day treatment with high doses of FLC-CY represented a clear proof of concept (4,11,28). The present work tested identical regimens, which, as in previous experiments, produced supratherapeutic blood FLC concentrations (i.e., trough levels up to 15 mg/liter, a concentration still compatible with that achieved with high-dose treatment in humans) and CY (i.e., trough levels up to 2.5 mg/liter, which is 5-to 10-fold the concentrations targeted in humans) (data not shown) (11).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro susceptibilities of the C. albicans 36082 s and 36082 r strains to FLU were determined by a previously published method (45). In the present study, an inoculum of 10 6 CFU/ml and an incubation temperature of 30°C were used to simulate readily achievable fungal densities and growth rates relevant to complex biomatrices, such as cardiac vegetations, respectively.…”
mentioning
confidence: 99%